2016
DOI: 10.1177/2325967116666039
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Revision Surgery After Primary Anterior Cruciate Ligament Reconstruction

Abstract: Background:Revision anterior cruciate ligament (ACL) reconstruction surgery occurs in 5% to 15% of individuals undergoing ACL reconstruction. Identifying predictors for revision ACL surgery is of essence in the pursuit of creating adequate prevention programs and to identify individuals at risk for reinjury and revision.Purpose:To determine predictors of revision ACL surgery after failed primary ACL reconstruction.Study Design:Case-control study; Level of evidence, 3.Methods:A total of 251 participants (mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 40 publications
5
58
1
1
Order By: Relevance
“…In a case-control study of 251 participants aged 26.1 AE 9.9 years, it was identified that allografts (OR: 2.37, 95% CI: 0.91-6.18) and patients younger than 18 years (OR: 9.52, 95% CI: 2.05-44.26) were a few of many predictors of revision surgery. 26 In this systematic review, two studies (n ¼ 99; 24.4%) compared the outcomes of allograft versus autograft ACLR. In a retrospective review of 534 primary ACLR cases aged 14.8 AE 1.1 (range: 11.3-16.9), the reported aseptic revision rates for BPTB autograft, hamstring autograft, and allograft (not specified) were 5.5, 7.5, and 13.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In a case-control study of 251 participants aged 26.1 AE 9.9 years, it was identified that allografts (OR: 2.37, 95% CI: 0.91-6.18) and patients younger than 18 years (OR: 9.52, 95% CI: 2.05-44.26) were a few of many predictors of revision surgery. 26 In this systematic review, two studies (n ¼ 99; 24.4%) compared the outcomes of allograft versus autograft ACLR. In a retrospective review of 534 primary ACLR cases aged 14.8 AE 1.1 (range: 11.3-16.9), the reported aseptic revision rates for BPTB autograft, hamstring autograft, and allograft (not specified) were 5.5, 7.5, and 13.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Even with the most accurate individualized, anatomic approach to ACL reconstruction, the potential for graft failure still exists, with reported retear rates as low as 5%, 2 and even higher in female athletes 3 or patients reconstructed with allograft. 4 One of the biggest challenges is how we translate the results from animal models to larger human models.…”
Section: See Related Article On Page 331mentioning
confidence: 99%
“…Several methods of ACL reconstruction using autografts or allografts of the hamstrings or patellar tendon have been under investigation in the last decades for the management of ACL tears [1, 7]. However, the long-term outcomes of current reconstruction methods remain unsatisfactory with high failure rates, thus revisions are necessary [8]. …”
Section: Introductionmentioning
confidence: 99%